Development Of A Village Information System Using The Spiral Method - Supiyandi, Supiyandi; Rizal, Chairul; Fachri, Barany; Eka, Muhammad; Nasution, Yusuf Ramadhan (International Conference on Sciences Development and Technology, 2022)
Tomuan Holbung Village is a village located in North Sumatra. As a village, there is still information that has not been accessed by many others through public communication, namely the internet. For this reason, it is necessary to develop an information system. Technology changes human life into quick and easy access to information data. Technology contributes to the arrangement of management systems and work processes in government and private institutions. One of the applications of Information Technology in village life is the use of the Village Information System (SID). In the development of this web-based village information system using the spiral method in development which consists of analysis, design, coding and testing as well as entity relationship diagrams in designing the database. The existence of a website-based village information system can facilitate devices in processing village information data to be more effective and efficient in providing information about village government in Tomuan Holbung Village. In addition, researchers also added features of activities that were widely informed. The Village information system is equipped with a web-based display so that users can adjust the contents in the system such as a web-based village information system as a means of information in web development in Tomuan Holbung Village using the spiral method.